Effect of Candesartan Usage on Uric Acid Levels : Pengaruh Penggunaan Candesartan Terhadap Kadar Asam Urat - Rumi, Amelia; Budiyanto, Titi Dwi Cahyani (Universitas Tadulako, 2023)
Cardiovascular disease is caused by disorders of the heart and blood vessels. One of the risk factors for cardiovascular disease is hyperuricemia, which indicates a high uric acid level in the blood, namely ≥7.0 mg / dL in men and ≥6.0 mg/ dL in women. Candersatan is one of the main line therapies that are widely used in cardiovascular patients which in previous studies were known to affect uric acid levels. This study aims to determine the effect of the use of candersatan on uric acid levels in cardiovascular patients for 3 months. This study uses a cross-sectional study with a prospective approach that is by examining uric acid levels before and after three months using candersatan and analyzed using SPSS statistical test Paired test. Of the total samples that met in the inclusion and exclusion criteria were 19 patients, the results showed an increase in uric acid levels with a significance value of 0,012 (p = ≤0.05). So it can be concluded that the average uric acid level of patients before using candersatan was 5.44 mg / dL, and the average uric acid level after using candersatan for three months was 6.30 mg / dL which means that the used of 8 mg candersatan for three months had a significant effect on the increase in uric acid levels in cardiovascular patients.